Impact of a family-based pulmonary rehabilitation program: an exploratory study - Marques, Alda (2014)
The World Health Organization has recommended family integration in rehabilitation interventions. Nevertheless, Pulmonary Rehabilitation (PR) programs for chronic obstructive pulmonary disease (COPD) remain focus on patients’ needs, neglecting the role of the family.